Post-therapeutic relapse of psoriasis after CD11a blockade is associated with T cells and inflammatory myeloid DCs. - Leanne M Johnson-Huang (Public Library of Science (PLoS), 2012)
Unlabelled To understand the development of new psoriasis lesions, we studied a group of moderate-to-severe psoriasis patients who experienced a relapse after ceasing efalizumab (anti-CD11a, Raptiva, Genentech). There were increased CD3(+) T cells, neutrophils, CD11c(+) and CD83(+) myeloid dendritic cells (DCs), but no increase in CD1c(+) resident myeloid DCs. In relapsed lesions, there were many CD11c(+)CD1c(-), inflammatory myeloid DCs identified by TNFSF10/TRAIL, TNF, and iNOS. CD11c(+) cells in relapsed lesions co-expressed CD14 and CD16 in situ. Efalizumab induced an improvement in many psoriasis genes, and during relapse, the majority of these genes reversed back to a lesional state. Gene Set Enrichment Analysis (GSEA) of the transcriptome of relapsed tissue showed that many of the gene sets known to be present in psoriasis were also highly enriched in relapse. Hence, on ceasing efalizumab, T cells and myeloid cells rapidly enter the skin to cause classic psoriasis. Trial registration Clinicaltrials.gov NCT00115076.